IS COOPERATIVE LEARNING BETTER THAN INDIVIDUAL LEARNING IN READING COMPREHENSION WORKSHOP? - Harjono, Hary Soedarto; Wachyunni, Sri - (Program Magister Teknologi Pendidikan Universitas Jambi, 2011)
The present study investigates effect of cooperative method on students’ achievements in reading comprehension in the context of English as a Foreign Language (EFL). An adaptation of the HAVO test was used to measure reading comprehension of 75 undergraduate students of the English Department at Jambi University. Participants were selected randomly assigned to three groups: two experimental groups and one control group. The experimental groups had been taught by means of the cooperative and an individual learning method in reading comprehension by means of workshops, whereas the control group had been taught by means of individual learning method with no workshops. A pre-test and post-test were administered, and the results were analyzed through a one-way ANOVA and post hoc Kruskal-Wallis Test followed by the Mann-Whitney Test. The results revealed that there was no significant effect in reading comprehension achievement in the cooperative group with workshops and in both of the individual groups. Keywords: cooperative and individual learning, reading comprehension